28 Retrospective pooled analysis of epacadostat clinical studies identifies doses required for maximal pharmacodynamic effect in anti-PD-1 combination studies. (9th November 2020) - Smith, Michael; Newton, Robert; Owens, Sherry; Gong, Xiaohua; Tian, Chuan; Maleski, Janet; Leopold, Lance
Abstract : Background: IDO1 is the initial rate-limiting enzyme in one breakdown pathway of tryptophan. It reduces tryptophan levels and generates metabolites (e.g., kynurenine [KYN]) that contribute to tumor-associated immune suppression. Epacadostat (EPA) is a novel, potent, selective, reversible inhibitor of IDO1 studied in clinical trials in combination with anti-PD-1 antibodies. Epacadostat-induced decreases in plasma KYN have been used as a pharmacodynamic measure of drug activity and have aided in dose selection for clinical studies. Despite encouraging signs of efficacy in combination with pembrolizumab (PMB) in the ECHO-202 study, a large phase 3 study in melanoma (ECHO-301) failed to reproduce this outcome. 1 Methods: Longitudinal plasma samples were obtained from participants in EPA clinical studies. Plasma KYN and EPA concentrations were measured by validated liquid chromatography tandem mass spectrometry. Quantitative mass spectrometry imaging (qMSI) of intratumoral tryptophan metabolites was also performed. Results: Analysis of plasma KYN levels demonstrated that PMB monotherapy significantly elevated KYN. While blocking the PMB-induced increase, EPA (100 mg BID) in combination with PMB failed to normalize KYN to healthy control levels as was reported for EPA monotherapy. 2 Because anti-PD-1 treatment can induce interferon gamma (IFN-γ) production and IDO1 expression is IFNg inducible, 3 we hypothesize that PMB-induced IFN-γ may be responsible for the observed increase of plasma KYN levels. Combined analysis of plasma KYN from additional EPA/anti-PD-1 combination (ECHO-202; EPA/PMB, ECHO-204; EPA/nivolumab) and monotherapy (ECHO-210) studies, with EPA doses ranging from 50 to 600 mg BID, suggested that higher EPA doses (≥600 mg BID) may be necessary to overcome the anti-PD-1–associated KYN elevation. Doses ≥600 mg BID are projected to cover the EPA IC90 value for 24h. The POD1UM-102 study is currently evaluating the combination of a novel anti-PD-1 monoclonal antibody (retifanlimab) plus EPA at doses up to 900 mg BID. Preliminary results from this study indicate that 600 mg BID is the maximally tolerated dose and is capable of maintaining suppression of KYN to healthy control levels through treatment cycle 4. Additionally, qMSI of paired pre-treatment and on-treatment biopsies demonstrated intratumoral suppression of KYN production with EPA 600 mg BID. Conclusions: Using suppression of plasma KYN as a pharmacodynamic marker of EPA activity, we demonstrated that maximal blockade of IDO1 activity in the context of anti-PD-1 treatment requires doses of EPA substantially higher than those tested in prior clinical studies. These findings are now informing additional proof of concept clinical studies. Acknowledgements: These studies were sponsored by Incyte Corporation (ECHO-210, POD1UM-102) and in collaboration with MSD (ECHO-301, ECHO-202) and Bristol Myers Squibb (ECHO-204). Trial Registration: ECHO-202 [NCT NCT02178722 ]; ECHO-204 [NCT02327078 ]; ECHO-210 [NCT01685255 ]; ECHO-301 [NCT02752074 ]; POD1UM-102 [NCT03589651 ] Ethics Approval: These studies were each approved by the institutional review board or independent ethics committee of participating institutions. References: Long GV, Dummer R, Hamid O, et al. Epacadostat plus pembrolizumab versus placebo plus pembrolizumab in patients with unresectable or metastatic melanoma (ECHO-301/KEYNOTE-252): a phase 3, randomized, double-blind study. Lancet Oncol 2019;20:1083–1097 Beatty GL, O'Dwyer PJ, Clark J, et al. First-in-human phase I study of the oral inhibitor of indoleamine 2, 3-dioxygenase-1 epacadostat (INCB024360) in patients with advanced solid malignancies. Clin Cancer Res 2017;23:3269–3276. Munn, DH, Mellor AL. IDO in the tumor microenvironment: inflammation, counter-regulation, and tolerance. Trends Immunol 2016;37:193–207.